KESULITAN BAHASA SISWA KELAS V SEKOLAH DASAR DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Pani Suswari, - (2020)
ABSTRAK Desain penelitian adalah study kasus. Subjeknya siswa kelas V SDPN 252 Bandung berjumlah 33 siswa. Hasilnya adalah kemampuan beberapa siswa memecahkan soal cerita berkategori sedang. Jenis kesulitan bahasa beberapa siswa adalah kesulitan dalam memahami kata, frasa, kalimat, dan konteks keseluruhan. Untuk mengatasi jenis kesulitan bahasa tersebut dengan pendekatan pengajaran grafik organizer dan memperhatikan prinsip utama pengajaran kata; penggunaan frasa sudah dikenal siswa; kalimat soal tidak terlalu panjang serta kalimat yang panjang dipecah menjadi pendek; penyajian konteks soal sudah dikenal siswa, modifikasi kronologi struktur soal dan penggunaan bahasa komunikatif; penggunaan grafik organizer modifikasi langkah Polya dan penggunaan pendekatakan pengajaran konsultatif. Keywords: Pemecahan masalah, kesulitan bahasa, dan soal cerita ABSTRACT The research design is a case study. The subjects were students of class V SDPN 252 Bandung totaling 33 students. The result is the ability of several students to solve the medium category story problems. Types of language difficulties for some students are difficulties in understanding words, phrases, sentences, and overall context. To overcome these types of language difficulties with a graphic organizer teaching approach and paying attention to the main principles of word teaching; the use of phrases already familiar to students; question sentences are not too long and long sentences are broken down into short ones; presenting the context of the questions already known to students, modifying the chronology of the question structure and using communicative language; the use of graphic organizer modification of Polya's steps and the use of a consultative teaching approach. Keywords: Problem-solving, language difficulties, and story problems